Design of a Pseudo-Real Time Microwave Imaging System for Cylindrical Dielectric Structures - Nasab, Soudeh Heyadri (2011)
A Master of Science Thesis in Electrical Engineering submitted by Soudeh Heyadri Nasabentitled, "Design of a Pseudo-Real Time Microwave Imaging System for Cylindrical Dielectric Structures," submitted in May 2011. Available are both soft and hard copies of the thesis.